Assembly and analysis of the complete mitochondrial genome of endangered plant Tilia amurensis Rupr - Liu, Xiao; Lin, Furong; Zhai, Shasha; Wu, Zhicheng; Gao, Lei; Sun, Nana; Yan, Wenchao; Chen, Jitong; Liu, Dan (Frontiers in Plant Science, 2025)
IntroductionTilia amurensis Rupr., a deciduous tree of the genus Tilia in the Malvaceae family, is classified as a second-class key protected wild plant in China. This study aimed to sequence and analyze the complete mitochondrial genome of T. amurensis to (i) aid the understanding of phylogenetic relationships within the Malvaceae family, (ii) clarify the taxonomic status of genus Tilia, and (iii) provide a molecular basis for the conservation and genetic breeding of this endangered species.MethodsT. amurensis mitochondrial genome was sequenced and assembled using the Illumina and Oxford Nanopore Technologies platforms. Additionally, bioinformatics analyses were conducted, along with gene annotation and functional analysis, to identify repeat sequences and chloroplast-derived fragments.ResultsThe assembled mitochondrial genome of T. amurensis was found to be a single circular molecule with a total length of 830,088 bp and a GC content of 44.97%. A total of 61 genes were annotated, including 20 tRNA, 3 rRNA, and 38 protein-coding genes. Moreover, 472 RNA editing sites were identified among the protein-coding genes. We also detected a high abundance of repetitive sequences and chloroplast-derived fragments. Specifically, the genome included 264 simple sequence repeats, 19 tandem repeats, and 855 pairs of scattered repeats, predominantly comprising short fragment repetitions. Furthermore, 22 chloroplast homologous fragments (with a cumulative length of 8,138 bp) were identified, accounting for 0.98% of the total mitochondrial genome length. Phylogenetic analysis based on the mitochondrial genomes of 35 plant species confirmed that T. amurensis, within the Malvaceae family of the Malvales order, is consistent with the latest classification proposed by the Angiosperm Phylogeny Group.DiscussionThis study reports, for the first time, the complete mitochondrial genome sequence of T. amurensis, revealing its high reproducibility and notable chloroplast-to-mitochondria DNA transfer. These findings provide valuable data for understanding the evolutionary dynamics of the Malvaceae mitochondrial genome. Furthermore, they establish a molecular foundation for future research on the endangerment mechanisms of T. amurensis, its genetic diversity, and development of effective conservation strategies.